Mapping Coffee Shops as Informal Cooling Spaces: Evidence from Land Surface Temperature and Urban Activity Patterns - Jhon Jhohan Putra K.D; Ahmad Farid Ardiansyah; Muhammad Bastian Akbar (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
This study explores the role of coffee shops as informal cooling spaces within the context of the Urban Heat Island (UHI) phenomenon in Jember, Indonesia. As a rapidly growing secondary city, Jember faces increasing thermal stress due to urbanization, limited green infrastructure, and uneven spatial development. While formal cooling strategies such as urban green spaces remain limited, coffee shops have emerged as accessible semi-public spaces that may contribute to thermal comfort in everyday urban life.This research adopts a quantitative spatial approach by integrating remote sensing and Geographic Information Systems (GIS). Land Surface Temperature (LST) was derived from Landsat 8 imagery to identify urban heat patterns, while coffee shop location data were collected from Google Maps and analyzed using Kernel Density Estimation to detect clustering patterns. An overlay analysis was conducted to examine the spatial relationship between coffee shop distribution and high-temperature zones. The results show that high LST areas exceeding 37°C are concentrated in densely built-up districts, particularly Sumbersari and Kaliwates, which are dominated by residential, commercial, and service activities. In contrast, lower temperature zones are associated with vegetated land uses such as rice fields, plantations, and community forests. Coffee shops exhibit a strong agglomeration pattern in urban cores, with significant hotspots identified in Sumbersari and secondary clusters in Kaliwates. The overlay analysis reveals that a substantial number of coffee shops are located within high-temperature zones, indicating a spatial alignment between areas of high cooling demand and the presence of these establishments.These findings suggest that coffee shops have the potential to function as informal cooling infrastructures, providing thermal refuge in dense urban environments. However, their uneven distribution also reflects spatial inequality, as peripheral areas have limited access to such amenities. This study highlights the importance of recognizing informal and privately operated spaces in urban heat mitigation strategies, particularly in secondary cities where formal cooling infrastructure is insufficient.